FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2015 - Riska Urip Lestari; Danar Irianto (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study aimed to examine the effect of firm size, liquidity, financial flexibility, share growth, sale growth, business risk and profitability to capital structure. This study used secondary data from the company’s financial statements and determinan of the sample using techniques proposive sampling. The population in this study are manufacture companies listed on the Indonesian Stock Exchange (BEI) in the period 2011-2015 with a sample 55 companies. The result showed firm size has a positive effect to capital structure. Liquidity has a no effect to capital structure. Financial flexibility has a negative effect to capital structure. Sale growth has a positive effe ct to capital structure. Profitabilitas has a negatife effect to capital structure. Other result showed share growth and risk business has no effect to capital stucture. The result of the study are expected to add to the research literature that discuss the factors that effect of capital structure on manufacture companies. Further research can add control variable. Key Words: Capital structure, Firm size, Liquidity, Financial flexibility, share growth, sale growth, business risk, Profitability